NANOBODIES: STRUCTURE, MANUFACTURING, APPLICATION (REVIEW) - A. V. Shatalova; A. S. Yakubova; V. V. Palimpsestov; I. B. Esmagambetov (Разработка и регистрация лекарственных средств)
Introduction. Single-domain antibodies (nanobodies) are composed of the heavy-chain variable domain only. Compared to conventional immunoglobulins G (IgG) nanobodies have such qualities as: high bioavailability, ability to bind epitopes that are difficult to reach, high solubility and thermal stability, etc. Nanobodies can be easily manufactured in microorganisms (E. coli) to significantly save on cost.Text. Goal of the paper consists of the description of structural and functional properties of nanobodies and its effective application.Conclusion. Nanobodies can be used in many fields of medicine and biotechnology such as research, diagnostics and therapy of oncology, infectious, hematological, inflammatory, autoimmune and neurological diseases. They can also be easily modified using another nanobody, molecules or radioactive mark as necessary. Nanobodies have huge potential for applications in diagnostics, therapy and medicine.